การชักนำให้เกิดการกลายในกล้วยหอม (Musa spp.) จีโนม AAA ด้วยรังสีแกมมาแบบเฉียบพลันและตรวจสอบด้วยเครื่องหมายแฮตอาร์เอพีดี - คาชิมา ศิริญยา; ธนานันต์ ธีระชัย; ขจรผดุงกิตติ ยงศักดิ์; โพธิปัทมะ กิตติ (Thai Journal of Science and Technology, 2020)
Natural breeding in banana is limited due to high sterility and parthenocarpic fruit. So, it gives low fertility when breeding. This study induced mutation in banana genus Musa which cultured in vitro and detected mutation by using HAT-RAPD. Musa cvs. ‘Kluai Hom Thong’, ‘Kluai Hom Thong Taiwan’ and ‘Kluai Hom Khieo’ tissues were cultured and radiated with acute gamma radiation at 0, 20, 40, 60 and 80 grays. These banana tissues were cultured on MS medium supplemented with 2 mg/L BA. It was found that all banana tissues were dead when radiated more than 40 grays. Tissues of ‘Kluai Hom Thong Taiwan’ and ‘Kluai Hom Khieo’ had 100 % survival rate when radiated with 20 grays while 80 % survival rate was obtained in ‘Kluai Hom Thong’. When studied LD30 in 3 types of banana, it was 8, 22.5 and 29.4 grays, respectively. This result showed that each types of banana had different types of tolerance with gamma radiation. This made banana tissues had different growth rates. The LD30 gave different mutation characteristics such as short leaf, leaf curl, stunt and pale pseudobulb. When detected their characters with HAT-RAPD technique by using primer E32, this method classifies the genetic differences in banana trees from treated and non-treated radiation.